Assemblies and composites of gold nanostructures for functional devices: Nanoscience: Special Issue Dedicated to Professor Paul S. Weiss. Issue 4 (14th June 2021) - He, Ke; Jiang, Ying; Wang, Ting; Liu, Zhihua; Wang, Ming; Pan, Liang; Chen, Xiaodong
Abstract: Gold has been one of the most vastly used noble metals due to its unique properties. In modern manufacturing, gold is extensively used in electronics industry as electrical connectors due to the high conductivity and corrosion resistance. With advancements in gold chemistry and nanofabrication technologies, gold materials can be tailored down to the dimension of nanoscale, which enables various novel properties. However, it is still a huge challenge to realize practical functional devices by rational utilizing these gold nanostructures‐based materials. Herein, the recent developments in the design and fabrication of various functional devices based on assemblies and composites of gold nanostructures are summarized. Starting from the plasmonic effect, optical colorimetric sensors, optoelectronics and surface‐enhanced Raman spectroscopy sensors are introduced. Followed by conductive devices with novel properties, flexible transparent conductors, stretchable electronics, wearable and implantable devices are discussed. Both bottom‐up and top‐down approaches to prepare assemblies and composites are covered. In addition, the challenges and future developments in the field are also addressed. It is believed that further developments in gold nanostructures‐based materials will greatly contribute to the next‐generation biosensors, optoelectronics, wearable and implantable electronics. Abstract : The design and fabrication of functional devices based on assemblies and composites of gold nanostructures are presented. In addition to traditional optical devices and optoelectronics, recently developed stretchable, wearable and implantable devices are also introduced. The review provides unique insights to gold nanostructures‐based materials and their potentials in the future biosensors, optoelectronics and wearable electronics.